ANALISIS BENTUK KERUSAKAN SORONGA PADA SITUS GUA PETI MATI DI DESA MATAHORI, KECAMATAN PADANGGUNI, KABUPATEN KONAWE - Anisa Anisa; Abdul Alim; Salniwati Salniwati (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study discusses the analysis of the form of soronga damage at the Coffin Cave site in Matahori Village, Padangguni District, Konawe Regency. In researching the problem of the forms of Soronga damage and how to deal with weathering and Soronga damage to the Coffin Cave site in Matahori Village, Padangguni District, Konawe Regency. By using a descriptive analysis approach using inductive reasoning forms. Collecting data in this study by conducting literature studies, observations, documentation and interviews and using the form of analysis that is applied is morphological analysis. The results of the study showed that the most dominant forms of damage encountered were biological weathering, influenced by weathering factors such as mosses, termites, fungi and human damage, namely antiquarians who plundered archaeological remains at the coffin cave site. Efforts to counteract the damage to Soronga include providing physical protection, such as conservation efforts, linking the role of the government in equitable upgrading, counseling related to cultural heritage objects, institutional development of Matahori village, and installing information boards on the coffin cave site.